Entrevista radial a Eugenio Espejo como precursor del periodismo en el Ecuador. - Chávez Rodríguez, Jacqueline Alexandra (2016)
The communicative product "Radio interview to Eugenio Espejo as Precursor of Journalism in Ecuador" aims to convey a different and dynamic the story about the beginning of journalism in our country, from the first paper entitled "Primicias de la Cultura de Quito" in 1792. This radio production has been prepared under a comprehensive literature research paper the same as have studied and written about the life of this character. It has also taken into account the Latin American theoretical Jesus Martín Barbero “of the media to mediations. Communication, Culture and Hegemony" with this radio interview intended to be a new option for information and culture for the listener. The radio interview to Eugenio Espejo will be transmitted through InRadio, the online radio career of Social Communication of the Salesian Polytechnic University in Quito, lasting 25 minutes, making this radio product will as public targeting students 18-25 years of age, where radio listeners relive the story just listen to this interview. This will be accomplished with the objective of using the media and journalistic formats in the recovery of historical memory and the generation of knowledge on topics of debate and citizenship.